2021
DOI: 10.1371/journal.pone.0257506
|View full text |Cite
|
Sign up to set email alerts
|

Urinary urgency acts as a source of divided attention leading to changes in gait in older adults with overactive bladder

Abstract: Aims There is a well-recognised but unexplained association between lower urinary tract symptoms including urgency and urgency incontinence and falls in older people. It has been hypothesised that urinary urgency acts as a source of divided attention, leading to gait changes which increase falls risk. This study aimed to assess whether urinary urgency acts as a source of divided attention in older adults with overactive bladder (OAB). Methods 27 community-dwelling adults aged 65 years and over with a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, a previous report showed falls to be more frequent in adults ≥65 years old (39.4%) with UUI compared with those without UUI 25 . Higher fall rates in this population may be partly due to a slower gait speed and increased variability in gait among older women (≥65 years) with severe UI experiencing urinary urgency 26,27 . As such, the significant improvements observed in this analysis with vibegron in both UUI episodes and urgency episodes suggest that vibegron may be a beneficial and safe treatment option among older women with OAB.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Furthermore, a previous report showed falls to be more frequent in adults ≥65 years old (39.4%) with UUI compared with those without UUI 25 . Higher fall rates in this population may be partly due to a slower gait speed and increased variability in gait among older women (≥65 years) with severe UI experiencing urinary urgency 26,27 . As such, the significant improvements observed in this analysis with vibegron in both UUI episodes and urgency episodes suggest that vibegron may be a beneficial and safe treatment option among older women with OAB.…”
Section: Discussionmentioning
confidence: 49%
“…25 Higher fall rates in this population may be partly due to a slower gait speed and increased variability in gait among older women (65 years) with severe UI experiencing urinary urgency. 26,27 As such, the significant improvements observed in this analysis with vibegron in both UUI episodes and urgency episodes suggest that vibegron may be a beneficial and safe treatment option among older women with OAB. Given the symptoms associated with OAB can be burdensome and significantly affect patient QoL, the International Continence Society recommends evaluating QoL measures in addition to symptom measures.…”
Section: N Original Researchmentioning
confidence: 69%
“…However, the underlying cause for this connection has been under some debate. Previously suggested simple rationale such as rushing to the toilet caused by the sense of urgency has been questioned [13,40], and the current evidence suggests that likely both UI and falls are markers of underlying vulnerability and disability [14,41,42]. Our results concur with these findings, given that our analysis was adjusted with considerable number of factors (many of which represent disability and vulnerability) and our selected study population consisted of participants with high level of disability as already demonstrated in our previous works [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that urinary urgency affects gait in older adults by diverting attention from the task of walking. A small study of older adults with overactive bladder ( n = 25) found that urinary urgency resulted in gait changes similar to those induced by a distracting task, and such changes increase risk for fall [ 39 ]. Additionally, anxiety and depression are also worse in women with UUI who have already suffered a fall.…”
Section: Association Between Urinary Incontinence and Falls In Older ...mentioning
confidence: 99%